2021
DOI: 10.1038/s41598-021-90031-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory influence of cationic Gemini surfactant on the dissolution rate of N80 carbon steel in 15% HCl solution

Abstract: Strong acids are commonly used in petroleum wells to remove scale layers from the surface of N80 C-steel pipe. The corrosive effects of these acids, on the other hand, pose a significant risk to C-steel pipes. For the first time, we discovered the anti-corrosion properties of cationic Gemini surfactant, 1,2-bis(dodecyldimethylammonio) ethane dibromide (DMAEB), for N80 C-steel pipe in acid washing solution (15.0% HCl). The DMAEB, in particular, can reduce the corrosion rate of N80 C-steel by approximately 97%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This spacer may be hydrophilic or hydrophobic, short or long, and rigid or flexible [14]. Gemini surfactants have been used as corrosion inhibitors for steel in different environments [15][16][17][18][19][20][21][22]. For instance, in [16] three imidazoline gemini surfactants were used as corrosion inhibitors for X-70 carbon steel in NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…This spacer may be hydrophilic or hydrophobic, short or long, and rigid or flexible [14]. Gemini surfactants have been used as corrosion inhibitors for steel in different environments [15][16][17][18][19][20][21][22]. For instance, in [16] three imidazoline gemini surfactants were used as corrosion inhibitors for X-70 carbon steel in NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…The potential uses and applications of Gemini surfactants lie in their unique physical properties, most notably their low cmcs (critical micelle concentrations), good wettabilities and surface tension lowering properties. Potential applications include oil spill remediation agents [1], anti-corrosives [2,3], antimicrobial and anti-algal agents [3][4][5][6] and gene therapy [8] to name a few. The major features governing the physical properties of a dicationic Gemini surfactant are:…”
Section: Introductionmentioning
confidence: 99%
“…Gemini surfactants owing to their ease of synthesis, low CMC, superior wetting, solubilizing, emulsifying and dispersing ability have gained research interest globally (Ahmady et al, 2022) Moreover, cationic esterquat Gemini surfactants have been found to have good biocidal activity owing to the presence two ammonium groups (Brycki et al, 2017; Laatiris et al, 2008). Considering the exceptional surface properties, Gemini surfactants have found potential applications in corrosion inhibition, gene delivery, drug delivery, enhanced oil recovery and various home and personal care formulations (Datir et al, 2021; Deyab & Mohsen, 2021; Fisicaro et al, 2014; Fu et al, 2016; Kaczerewska et al, 2018; Kamal, 2015; Liu et al, 2020; Mahajan et al, 2012; Patil et al, 2023; Rajput et al, 2018, 2020). In addition to aforesaid applications, Gemini surfactants are proven to have excellent biological activity and anti‐microbial properties (Aiad et al, 2013; Labena et al, 2020; Shaban et al, 2014, 2016, 2018; Shaban & Kim, 2020).…”
Section: Introductionmentioning
confidence: 99%